HUBUNGAN ANEMIA DAN KEKURANGAN ENERGI KRONIK DENGAN KEJADIAN BBLR - Susiyanti, Susiyanti; Ariesti, Nining; Samal, Delila (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Low birth weight (LBW) is a baby's weight of less than 2500 grams at birth and can interfere with intrauterine growth. Maternal factors that can influence include chronic energy deficiency (CED) and anemia. Food intake consumed during pregnancy affects the incidence of CED and anemia. Cases of LBW in Indonesia are still quite high. Objective: This study was to determine the relationship between anemia and chronic energy deficiency and anemia with the incidence of LBW at Labuang Baji Regional Hospital in 2025. Method: This study is a quantitative study with a cross-sectional approach and a sample of 35. In the working area of Labuang Baji Regional Hospital, samples were obtained from hospital medical records from March to May 2025. The sampling technique was accidental sampling. The research data were tested with chi-square. Results: The analysis test showed a relationship between anemia and chronic energy deficiency with LBW with a P value of 0.005 and anemia with LBW with a P value of 0.004. Conclusion: In this study, anemia and KEK have an influence on LBW..